The Effectiveness of Community Responsiveness in the Digital Population Identity Program in Surabaya City - Linda Anggraini Hanti Meisya; Sri Roekminiati; Amirul Mustofa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digital Population Identity (DPI) is one of the application program innovations created by the Directorate General of Population, as DPI will be a replacement for physical Identity Card which will be carried out in a process or in stages. The aim of this research is to describe how effective the community's responsiveness is regarding the DPI application program as a form of Identity Card reprinting service. We also want to know what problems exist in this DPI application innovation when it is applied to the community. This is the goal as well as community support for the service. DPI. This research uses descriptive qualitative methods, data collection uses observation, and also in-depth interviews with the community. The results of this research show that not all people responded positively to the DPI application which was implemented as a reprinting requirement Identity Card so there is quite a lack of implementation of this DPI application innovation to the people of Pegirian Village because there are so many people who are classified as underprivileged and have low education so there is a lack of followingupdate The existing population and civil registration technology in Indonesia is quite realized and quite optimal, both in terms of the Service Operational Standards implemented by the City of Surabaya. This has resulted in a lack of conduciveness for the public in creating the latest application as one of the conditions for reprinting the Klampid New Generation (KNG) application as documentation for making DPI